Analisis Faktor yang Berhubungan dengan Resiko Depresi pada Lansia Diabetes Melitus di Wilayah Kerja Puskesmas Bandar Baru Kabupaten Pidie Jaya - Azhar Mualim; Novita Sari; Nurlela Mufida; Lisnawati Rahayu; Varla Nazila (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
People with diabetes often experience ongoing anxiety due to concerns about possible complications. This condition can have a negative impact on physical, psychological, and social health. This anxiety can develop into depression. This study aims to determine the factors associated with the risk of depression in elderly people with diabetes mellitus in the Bandar Baru Health Center Working Area, Pidie Jaya Regency. The type of research used is analytical with a cross-sectional approach, while data analysis used univariate and bivariate. The population in this study amounted to 473 elderly people and the sample was 83 people with a purposive sampling technique. Based on the results of the study, it is known that the majority of respondents experienced a risk of severe depression (48.2%), there is a significant relationship between the level of family support (p value = 0.000), family function (p value = 0.000), and family role (p value = 0.000) to the level of depression in elderly people with diabetes mellitus in the Bandar Baru Health Center Work Area, Pidie Jaya Regency, so it can be concluded that family support, family function and family role are related to the risk of depression in elderly people with diabetes mellitus in the Bandar Baru Health Center Work Area, Pidie Jaya Regency.